Vestibular Dysfunction in Turner Syndrome: A Case Report - Baxter, Michael (Otol Neurotol, 2014)
OBJECTIVE: Turner syndrome is a well-known cause of sensorineural hearing loss, and the lack of estrogen has been implicated in cochlear dysfunction. It has never been associated with vestibular dysfunction. We report a case of a patient with Turner syndrome who was found to have bilateral vestibular dysfunction based on video-oculography (VOG) testing. PATIENT: A single patient with a history of Turner syndrome who was found to have significant bilateral vestibular dysfunction. INTERVENTION: After noticing a deficit in the vestibulo-ocular reflexes on qualitative horizontal head impulse examination, the patient underwent VOG testing. MAIN OUTCOME MEASURE: VOG testing quantatively measures angular vestibulo-ocular reflex (AVOR) gain in the horizontal semicircular canal plane. AVOR gain represents the eye movement response to a head movement; in normal individuals the eye movement is fully compensatory and gain values are close to unity. RESULTS: VOG results showed AVOR gains of 0.29 and 0.36 on the right and left sides, respectively. CONCLUSION: We have presented a case of a woman with Turner syndrome with asymptomatic vestibular dysfunction demonstrated with VOG testing. Although there is a documented relationship between Turner syndrome and sensorineural hearing loss, there are no previous studies or case reports linking Turner syndrome and vestibular dysfunction. Additional research and added vigilance in monitoring Turner syndrome patients may be warranted.